Unique N doped Sn3O4 nanosheets as an efficient and stable photocatalyst for hydrogen generation under sunlight - Balgude, Sagar; Sethi, Yogesh; Gaikwad, Aarti; Kale, Bharat; Amalnerkar, Dinesh; Adhyapak, Parag (Nanoscale, 2020)
Unique N doped Sn3O4 nanosheets have been demonstrated successfully using a facile hydrothermal method. Investigations of the triclinic phase and the impurities were performed using powder X-ray diffraction analysis (XRD) and Raman spectroscopy. The morphological analysis demonstrated a rectangular intra- and inter-connected nanosheet-like structure. The length of the nanosheets was observed to be in the range of 200-300 nm and the thickness of the nanosheets was less than 10 nm. The optical study reveals an extended absorption edge into the visible region, owing to the incorporation of nitrogen into the lattice of Sn3O4, which was further confirmed using X-ray photoelectron spectroscopy (XPS). Considering the band structure in the visible region, the photocatalytic activities of pristine and N doped Sn3O4 nanosheets for hydrogen evolution from water under natural sunlight were investigated. 4% N-Sn3O4 showed a higher photocatalytic activity (654.33 mu mol(-1) h(-1) 0.1 g(-1)) for hydrogen production that was eight times that of pristine Sn3O4. The enhanced photocatalytic activity is attributed to the inhibition of charge carrier separation owing to the N doping, morphology and crystallinity of the N-Sn3O4 nanostructures. A stable efficiency was observed for three cycles, which clearly shows the stability of N-Sn3O4.